Shifting References: Celebrations of Uprisings in Croatia, 1945-1991 - Roksandić, Drago (Array, 1995)
Based on the research of the ways the uprisings were celebrated in Croatia in the period from 1945 to 1991 the author draws numerous conclusions on the contemporary ideologies.